Facile synthesis of N-doped 3D graphene aerogel and its excellent performance in catalytic degradation of antibiotic contaminants in water. (April 2019) - Wang, Jun; Duan, Xiaoguang; Dong, Qi; Meng, Fanpeng; Tan, Xiaoyao; Liu, Shaomin; Wang, Shaobin
Abstract: 3D nitrogen-doped graphene aerogels (NGA) with hierarchically porous architectures and integrated macrostructures were facilely constructed by self-assembly of graphene oxide (GO) nanosheets and melamine. NGA exhibited excellent catalytic activities in peroxymonosulfate (PMS) activation for oxidative degradation of ibuprofen (IBP). NGA attained 44- and 8-fold enhancement in reaction rate over graphene aerogel (GA) and N-doped reduced graphene oxide (NrGO), respectively. Furthermore, the chemical reactivity of NGA could be facilely recovered by thermal annealing. The superior catalysis of NGA can be ascribed to the synergistic effects of 3D porous framework and N-doping in sp 2 -hybridized NGA. Graphitic N is demonstrated to be the intrinsic active sites in PMS activation. The 3D porous architecture is beneficial for adsorption and diffusion of the pollutant/oxidant and graphitic carbons within the conjugated π system facilitate the electron transfer. Electron paramagnetic resonance and radical quenching tests indicate that NGA/PMS is a radical-based system, where SO4 − and OH with strong oxidative potentials account for the catalytic degradation of IBP. This study affords an innovative strategy for development of promising metal-free catalysts towards better advanced oxidation processes. Graphical abstract: Image 1